PENGARUH RASIO AKTIVITAS TERHADAP PROFITABILITAS PADA PERUSAHAAN FOOD AND BEVERAGES - Sodiq, Arif Mahfud; Fitria, Astri (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to find out the influence of account receivable turnover, inventory turnover, fixed asset turnover, total assets turnover and sales growth both simultaneous and partial to the profitability (ROA). The samples are food and beverages companies which are listed in Indonesia Stock Exchange (IDX) in 2010-2013 periods. 10 companies have been selected as samples. These samples have been selected by using purposive sampling. The multiple linear regressions is used as the data analysis technique. The hypothesis test has been done by using t-test to examine the regressions coefficient of each variable. The significance test has been carried out by using F test to examine the suitability of independent variable to the profitability variable with 5% level of significance. Based on the result of the data analysis of t-test, it can be concluded that the account receivable turnover, inventory turnover, fixed asset turnover, total asset turnover and sales growth do not have any significant influence to the Profitability (ROA) whereas fixed asset turnover give significant influence to the Profitability (ROA).Keywords: Account Receivables Turnover, Inventory Turnover, Asset Turnover, Sales Growth, and Profitability (ROA).